Optimasi Lip Balm Minyak Geranium (Pelargonium graveolens) Menggunakan D-Optimal Mixture Design - Meisya Ghina Shulhani; Budi Prabowo Soewondo; Ratih Aryani (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. Angular cheilitis is a lesion occurring at the corners of the lips and is commonly associated with Candida albicans infection. Geranium essential oil (Pelargonium graveolens) has potential antifungal properties and can be developed in lip balm formulations. This study aimed to determine the optimum formulation of a geranium essential oil lip balm stick and to evaluate its physical quality and stability using the D-optimal mixture design method. The lip balm base consisted of beeswax, carnauba wax, candelilla wax, shea butter, castor oil, and olive oil. The optimization results showed that the optimum formulation contained 23.4% beeswax, 3.3% carnauba wax, 3.3% candelilla wax, 20% shea butter, 40% castor oil, 10% olive oil, 0.1% BHT, 0.5% phenoxyethanol, and 0.5% geranium essential oil, with predicted melting point and hardness values of 65.77 °C and 393.83 g, respectively. The optimum formulation produced a homogeneous lip balm with a yellowish-white color and a characteristic geranium aroma without rancid odor. The pH value of the formulation was 5.0, which was within the physiological pH range of the lips. The melting point and hardness values were 66.67±0.29 °C and 406.67±5.77 g, respectively, meeting the physical quality requirements for lip balm preparations. Stability testing over three cycles showed no changes in texture, color, or aroma. Therefore, the geranium essential oil lip balm fulfilled the physical quality and stability requirements for cosmetic preparations. Abstrak. Cheilitis angular merupakan lesi pada sudut bibir yang sering dikaitkan dengan infeksi jamur Candida albicans. Minyak atsiri geranium (Pelargonium graveolens) diketahui memiliki potensi antijamur sehingga berpeluang dikembangkan dalam sediaan lip balm. Penelitian ini bertujuan untuk menentukan formula optimum lip balm mengandung minyak atsiri geranium serta mengevaluasi mutu fisik dan stabilitas sediaannya menggunakan metode D-optimal mixture design. Basis lip balm diformulasikan dari kombinasi beeswax, carnauba wax, candelilla wax, shea butter, castor oil, dan olive oil. Hasil optimasi menunjukkan formula optimum terdiri atas beeswax 23,4%, carnauba wax 3,3%, candelilla wax 3,3%, shea butter 20%, castor oil 40%, olive oil 10%, BHT 0,1%, fenoksietanol 0,5%, dan minyak atsiri geranium 0,5% yang diprediksi memiliki titik leleh sebesar 65,77 °C dan kekerasan sebesar 393,83 g. Formula optimum menghasilkan sediaan yang homogen, berwarna putih kekuningan, dan memiliki aroma khas geranium tanpa bau tengik. Nilai pH sediaan sebesar 5,0 berada dalam rentang fisiologis kulit bibir. Titik leleh sediaan sebesar 66,67±0,29 °C dan nilai kekerasan sebesar 406,67±5,77 g memenuhi persyaratan mutu fisik lip balm. Uji stabilitas selama tiga siklus menunjukkan tidak adanya perubahan tekstur, warna, maupun aroma sediaan. Dengan demikian, sediaan lip balm minyak atsiri geranium memenuhi persyaratan mutu fisik dan stabilitas sediaan kosmetik.